The Diversity and distribution of diurnal butterflies (Lepidoptera: Rhopalocera) in five categories of vegetation and two strata of forest (understory-subcanopy) in the Bosque Protector Cerro Blanco, Province of Guayas, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2014)
The dynamic of the communities of diurnal butterflies in the Bosque Protector Cerro Blanco (BPCB), a dry forest of the Ecuadorian coast is studied. Two type of collections have been used, the hand net and Van Someren-Rydon (VSR) traps. In addition, it has been studied the influence of five vegetation categories in vertical-horizontal dimensions and its influence on the diversity. The results are compared with other works carried out in the moist forest of the Ecuadorian Amazon. The total richness of butterflies present in BPCB is of 77 species, 23 from these species were collected with VSR traps, two species are unique from subcanopy, five species are unique from understory and 16 species are present in both strata. This is the first work of spatial distribution in a dry forest of Ecuador and is a contribution to the knowledge of the Lepidoptera of the country.
Keywords: Dry forest; collections; lepidoptera; rhopalocera; stratification; Van Someren-Rydon traps